Proceedings of the 12th International Conference on Hypernuclear and Strange Particle Physics (HYP2015) 2017
DOI: 10.7566/jpscp.17.021005
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Hypertriton Lifetime at STAR

Abstract: A precise measurement of the hypertriton lifetime and the ratio between the branching ratios of its two main decay channels has been made through the two body and three body decay channels with data of Au+Au collisions at √ s NN = 7.7, 11.5, 19.6, 27, 39

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The hypertriton or/and anti-hypertriton have been studied using ultra-relativistic heavy-ion collisions by the HypHI collaboration so-called Phase 0, at the Heavy Ion Accelerator Facility of GSI (the GSI Helmholtz Center for Heavy Ion Research) (see Box 2), the STAR collaboration at the Relativistic Heavy Ion Collider (RHIC) at the Brookhaven National Laboratory (BNL) and the ALICE collaboration at the Large Hadron Collider (LHC) at CERN. The recently derived hypertriton lifetime by the HypHI Phase 0 experiment 11 , STAR [12][13][14][15] and ALICE 16,17 together with the new measurement of the hypertriton binding energy by ALICE 18 have shown that the nature of the hypertriton can differ from the previous understanding. Furthermore, a signature of the unexpected Λnn bound state has been observed 19 by HypHI , but theoretical considerations do not predict the existence of this bound state, and whether or not the Λnn bound state can exist should also be experimentally clarified.…”
Section: [H1] Puzzles Of Hypernucleimentioning
confidence: 99%
See 1 more Smart Citation
“…The hypertriton or/and anti-hypertriton have been studied using ultra-relativistic heavy-ion collisions by the HypHI collaboration so-called Phase 0, at the Heavy Ion Accelerator Facility of GSI (the GSI Helmholtz Center for Heavy Ion Research) (see Box 2), the STAR collaboration at the Relativistic Heavy Ion Collider (RHIC) at the Brookhaven National Laboratory (BNL) and the ALICE collaboration at the Large Hadron Collider (LHC) at CERN. The recently derived hypertriton lifetime by the HypHI Phase 0 experiment 11 , STAR [12][13][14][15] and ALICE 16,17 together with the new measurement of the hypertriton binding energy by ALICE 18 have shown that the nature of the hypertriton can differ from the previous understanding. Furthermore, a signature of the unexpected Λnn bound state has been observed 19 by HypHI , but theoretical considerations do not predict the existence of this bound state, and whether or not the Λnn bound state can exist should also be experimentally clarified.…”
Section: [H1] Puzzles Of Hypernucleimentioning
confidence: 99%
“…However, the value overlaps with the free Λ-lifetime within a standard deviation 12 . Later, STAR remeasured the hypertriton lifetime by considering its three-body decay channel to a proton (p), a deuteron (d) and pion (π − ), 3 Λ H → p + d + π − , and discovered a significantly smaller value 13 , 155 +25 −22 (stat.)±31(syst.) ps .…”
Section: [H3] Mystery Of the Hypertritonmentioning
confidence: 99%
“…Therefore, the lifetime of the hypertriton has been considered to be very close to the lifetime of a free 𝛬 hyperon, i.e., 263 ps [12], without having precise experimental data. However, recent experiments employing heavy ion beams have shown much or slightly shorter lifetime values of hypernuclei than that of the free 𝛬 hyperon [13][14][15][16][17][18][19][20], and the measured values have a large span for measurements obtained even by one collaboration. Another type of three-body hypernuclear states have also become to be of special interest.…”
Section: Introductionmentioning
confidence: 99%